Effect of Reconstruction Activities on English Writing Skills: Mechanical Accuracy I (Punctuation) and Mechanical Accuracy II (Spellings) - Rauf, Abdul; Saeed, Muhammad (Journal of Education and Educational Development, 2021)
This study was aimed to explore the effect of reconstruction activities on grade XI students’ English writing skills mechanical accuracy I (Punctuations) and mechanical accuracy II (Spellings). Pre-test post-test control group experimental design was selected for the study. A public sector degree college for boys of district Lahore was selected conveniently for intervention. A sample of sixty (60) students out of 400, enrolled in the session 2018-19, was selected randomly. These 60 students were randomized into two equal groups (experimental and control). Experimental group was taught till 16 weeks continuously. Students’ English writing skills were measured through supply type achievement test. Results revealed that reconstruction activities had positive effect on students’ English writing skills. English teachers of grade XI were recommended to practice reconstruction activities for the development of English writing skills. Students of grade XI were recommended to practice reconstruction activities to develop their English writing skills.
Keywords: mechanical accuracy, punctuation, reconstruction activities, spellings, writing skills.